Mucopolysaccharidosis Type II (Hunter Syndrome): Clinical Picture and Treatment - Beck, Michael (Current Pharmaceutical Biotechnology, 2011)
Mucopolysaccharidosis (MPS) type II (Hunter syndrome, OMIM 309900) is an X-linked lysosomal storage disorder caused by a deficiency of the lysosomal enzyme iduronate-2-sulfatase (IDS). Major clinical manifestations include joint contractures, obstructive and restrictive airway disease, cardiac disease, skeletal deformities and often mental retardation. As with all the MPS disorders, mucopolysaccharidosis type II is a clinically heterogeneous disease in terms of the extent and rate of progression of organ impairment in affected individuals. Common causes of death, which usually occurs within the second decade of life, are obstructive airway disease and cardiac failure due to valvular dysfunction, pulmonary hypertension and myocardial disease. Patients with the more attenuated (so-called adult) form usually have a normal intelligence, but often have many complaints such as progressive loss of vision due to retinal dysfunction, spastic paresis due to myelon compression at the cranio-cerevical region, severe hip disease and cardiac complications. Clinical investigations that have been performed in the last years in a great number of patients have shown that many of these complications are still underdiagnosed and untreated. Until recently, no specific treatment was available for the affected patients; management mainly consisted of supportive care and treatment of complications. Enzyme replacement therapy with recombinant iduronate-2-sulphatase (idursulfase), however, has now been introduced. And it could be demonstrated that weekly intravenous infusions of idursulfase is able to improve many of the symptoms and signs of Hunter syndrome. This review will present the efficacy and safety data of the enzyme preparation and discuss benefits and limitations of this new therapeutic option.
Keywords: lysosomal enzyme iduronate-2-sulfatase (IDS)